Secularismo e religião na democracia deliberativa de Habermas: da pragmática ao déficit ontológico e metafísico - Oliveira, Juliano Cordeiro da Costa (2017)
The problem to be raised in this thesis is that there is, in Jürgen Habermas’ philosophy, an ontological deficit (a lack of a theory of the beings) and also a metaphysical déficit (the lack of a theory of the Being). Habermas’s thinking would, as far as we are concerned, be reduced to pragma- tics, leaving no room to the deepening of ontological and metaphysical questions, which Habermas himself implicitly suggests, although without further elaboration, for remaining faithful to his post-metaphysical thinking. Anyway, what are the consequences of such thinking for his proposal of a dialogue between secularism and religion in the deliberative democracy and even for his analysis of a religious phenomenon? The ontological and metaphysical deficit, first analyzed in the theoretical philosophy, in Truth and justification, would equally run its political philosophy, once Habermas does not reflect on the universal character of the good, in his defense of the ethics of the righteous. Finally, the ontological and metaphysical deficit would also reach its analysis of religious discourses, restricted to pragmatics, although Habermas recognizes the importance of religions when they translate their essential intuitions into a public and secular language. Puntel, in this sense, highlights a theoretical question, which leads him to rightly affirm that metaphysics is the instance in which the contents of religion is articulated. Since Habermas’ problem is purely pragmatic, that is, how to enable a dialogue between believers and non-believers, he does not take into account the metaphysical dimension of religion, but only its ethical contents. It is essential, in this context, to clearly distinguish two questions that appear in Habermas. 1) A theoretical problem: Habermas accepts the centrality of the language in a theory, although it has a unilateral analysis of the language, by reducing it into an analysis of the pragmatic dimension of the language; 2) A practical problem, he wonders: How may coexistence between believers and non-believers in a pluralistic and democratic society be possible? Thus, in Habermas, several questions can be eva-luated both in the light of philosophy and sociology. However, this fact also brings a series of confusions not only of Habermas’ himself, but also of his interpreters and critics, since the questions, no matter wheather they are philosophical or sociological, they are exposed as being of the same type. An example of such theme is religion, which now appears from a sociological point of view of a theory of society, sometimes through a philosophical and properly theoretical bias. Our work, however, is strictly philosophical, once in our view there would be an ontological and metaphysical deficit in Habermas’ ways of thinking, with consequences in his limited analysis of the religious phenomenon, restricted to the pragmatic dimension of the language.